ON THE HISTORY OF GRAMMAR-DICTIONARY - Bashorat Madiyevna Bakhriddinova; Gulnoza Khalilovna Khidirova (Galaxy International Interdisciplinary Research Journal, 2022)
The article deals with dictionaries, textbooks that serve as ancient school textbooks, their historical roots and developmental stages.